Diversifikasi the chili (Capsicum Annum) Plant Picnic Rubber (Havea Brasiliensis) Kanagarian Ampang Kuranji District Koto Baru, Dharmasraya. - Rafika, Irda; Dasrizal, Dasrizal; Thesiwati, Aslan Sari (STKIP PGRI Sumbar, 2013)
Research for this purposes get the data and information in one about chili (Capsicum Annum) plant Diversifikasi picnic rubber (Havea Brasiliensis) Kanagarian Ampang Kuranji district Koto Baru, Dharmasraya.Research for this type of research category Depth Kualitatif. Informan research taken in one Snowball sampling (Originally in a little, be Goose) is based on the same research sample characteristics spesific, the Filter is con sidered related with chili RAISING Picnic in the rubber. Informan this research are the farmers Plant rubber filter rubber Picnic in the chili.By research result Get node Following severar aspects: 1) How to grow chili picnic in the First rubber first taken ore sae chili, chili settings that ore FRUIT is made up raw for the origin, spread before origin, picnic in the rubber down clean planting origin chili, 2) How origin chili that comes down to bathing seeds and chili Filter raw bother with pests to pesticide plan in order chili, chili Plant grown with good, 3) Production results chili like Rock planr rubber quite profitability for farmers due to very satisfactory results than Get meet the needs day-day chili Get it for sale.